Introduction to electricity and magnetism : solutions to problems - Walecka, John Dirk, 1932- (New Jersey : World Scientific, 2019)
"The previously published textbook Introduction to Electricity and Magnetism provides a clear, calculus-based introduction to a subject that together with classical mechanics, quantum mechanics, and modern physics lies at the heart of today's physics curriculum. The lectures, although relatively concise, covers from Coulomb's law to Maxwell's equations and special relativity in a lucid and logical fashion. The book also contains an extensive set of accessible problems that enhances and extends the coverage, so the present book, as an aid to teaching and learning, provides the solutions to those problems"--
Electricity -- Coulomb's law -- The electric field -- Gauss' law -- The electrostatic potential -- Electric energy -- Capacitors and dielectrics -- Currents and Ohm's law -- DC circuits -- Review of electricity -- Magnetism -- Vectors -- The magnetic force and field -- Ampere's law -- Electromagnetic induction -- Magnetic materials -- Time-dependent circuits -- Review of magnetism -- Electromagnetism -- Maxwell's equations -- Waves -- Electromagnetic waves -- More electromagnetic waves -- The theory of special relativity -- Review of electromagnetism.
Includes bibliographical references and index.
Keywords: Electricity -- Problems, exercises, etc; Magnetism -- Problems, exercises, etc